Effect of aqueous garlic (Allium sativum) extract against di‐(2‐ethylhexyl) phthalate induced reproductive toxicity in male mice. (7th June 2022) - Iram, Fatima; Batool, Sajida; Shameem, Sitara; Aslam, Iqra; Batool, Saira; Shaheen, Marrium; Aziz, Riqza
Abstract: This study was designed to investigate testicular and male reproductive tract histopathologies and lipid profile against di‐ethylhexyl phthalate (DEHP) exposure in mice and curative potentials of aqueous garlic ( Allium sativum) extract. Four groups (n = 10) were named and treated as follow (a) control (C): (normal feed and drinking water + 0.2 ml corn oil); (b) aqueous garlic extract group (AGE): (500 mg/kg body weight of aqueous garlic extract); (c) DEHP group: (500 mg/kg body weight of DEHP, dissolved in corn oil; (d) AGE + DEHP group (500 mg/kg body weight garlic aqueous extract, and DEHP 500 mg/kg body weight dissolved in corn oil). The doses were given once daily through gavages for 28 days and on the 29th day, all the animals were euthanized through cervical dislocation and reproductive organs and blood samples were collected. The results showed that exposure to DEHP caused a significant effect on body weight, testicular weight, serum cholesterol, triglycerides, lipid profile, average cross‐sectional area (ACSA) of the seminiferous tubule, ACSA of the lumen of seminiferous tubule, spermatogenic cells, Leydig's cells number, vas deferens diameter, lumen, muscular thickness, and epithelial cell height of vas deferens. This study revealed that exposure to DEHP can be injurious to male reproductive health and aqueous garlic extract can decrease the toxic effects of DEHP in male mice.